PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA TENTANG MATERI PANCASILA SEKOLAH DASAR NEGERI 1 GESIKAN TAHUN PELAJARAN 2025/2026 - Vicky Patmawati; Sri Suwartini; Nela Rofisian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on Pancasila Education learning outcomes in Pancasila material for fifth-grade students at SD Negeri 1 Gesikan in the 2025/2026 academic year. This research employed a quantitative approach with an experimental design involving experimental and control classes through a pretest-posttest procedure. Data were collected through tests, observations, and documentation, then analyzed using normality, homogeneity, Independent Sample t-test, and N-Gain tests. The results showed a significant effect of PBL implementation on students’ learning outcomes, indicated by a significance value of 0.000<0.05 and |tcount|11.478>ttable2.026. The experimental class obtained an N-Gain score of 83.70% (high), higher than the control class at 29.93% (low). These findings indicate that PBL effectively improves understanding, active participation, critical thinking, and learning outcomes in Pancasila Education. The study implies that PBL can serve as an innovative alternative to improve contextual, participatory, and meaningful learning while strengthening Pancasila values in elementary schools.